2010
DOI: 10.1016/j.ceb.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Growth and division—not a one-way road

Abstract: SummaryMaintaining cell size homeostasis and regulating cell size in response to changing conditions is a fundamental property of organisms. Here we examine the recent advances in our understanding of the interplay between accumulation of mass (growth) and the progression through the cell cycle (proliferation), the coordination of which determines the size of cells. It is well established that growth affects cell division (reviewed in [1]). This review will focus on the reverse, less welldefined relationship -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…Our studies suggest that this reported colocalization may result from direct (or indirect) physical interaction. In addition, Goranov et al have suggested that direct regulation of actin remodeling may be an important biochemical mechanism for eukaryotic cell size control (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies suggest that this reported colocalization may result from direct (or indirect) physical interaction. In addition, Goranov et al have suggested that direct regulation of actin remodeling may be an important biochemical mechanism for eukaryotic cell size control (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The second mechanism in which cell division inhibits cell growth comes from studies in yeast and mammalian cells [148]. By measuring a single cell growth rate during the cell cycle progression in both yeast and mammalian cells, several groups have discovered that the cell growth rate during the cell cycle is not constant but changes during the cell cycle stages.…”
Section: Interaction Between Cell Growth and Cell Division In Cell Anmentioning
confidence: 99%
“…The first mechanism is that cell growth is dominant to cell division [115]. The second mechanism is that cell proliferation inhibits cell growth during the cell cycle [148]. The third mechanism is that cell growth and cell division are controlled coordinately by a growth coordinator.…”
Section: Interaction Between Cell Growth and Cell Division In Cell Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The maturation process involves, among other things, the melanization of the appressorium, the generation of internal turgor pressure, and the deposition of cytoskeletal components at the base of the appressorium pore to allow the formation of the penetration peg, where all the turgor pressure will be focused [64]. As mitotic growth arrest is thought to help cells to reorganize their structure and adapt to the increased energy demands needed for subsequent cell division or regeneration [65], it makes sense to stop cell wall expansion in the appressorium to allow maturation to proceed. The next step during the formation of a functional appressorium is the remodeling of the F-actin cytoskeleton to form a toroidal network at the base of the appessorium, which is organized by septins.…”
Section: Invasion Tools: Appressorium Formation and Cell Cycle Regulamentioning
confidence: 99%